Optimalisasi Peran Pemuda Karang Taruna dalam Edukasi Pencegahan HIV/AIDS Melalui Aplikasi Digital - Ariani, Resti; Rina Puspita; M Ulin Nuha; Choiry Amalya; Rery Renita; Tedy H Wijaya (UNIVERSITAS NGUDI WALUYO, 2025)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) remain a global health threat, with young people being the most vulnerable population. This activity aims to increase the knowledge, attitudes, and roles of Karang Taruna Catur Bina Taruna youth in HIV/AIDS prevention education through digital applications. The training involved 25 participants. The implementation method included interactive socialization and training on the use of educational applications. Evaluation through pre-tests and post-tests showed a 32% increase in knowledge, a 25% increase in attitudes towards people living with HIV/AIDS, and a 31% increase in willingness to become education agents. The results indicate that a digital-based approach is effective in improving youth health literacy and building community change agents. For sustainability, it is necessary to develop more interactive application features and collaborate with local health centers. ABSTRAK Human Immunodeficiency Virus (HIV) dan Acquired Immune Deficiency Syndrome (AIDS) masih menjadi ancaman kesehatan global, dengan kelompok usia muda sebagai populasi yang rentan. Kegiatan ini bertujuan meningkatkan pengetahuan, sikap, dan peran pemuda Karang Taruna Catur Bina Taruna dalam edukasi pencegahan HIV/AIDS melalui aplikasi digital. Peserta pelatihan sejumlah 25 orang. Metode pelaksanaan meliputi sosialisasi interaktif dan pelatihan penggunaan aplikasi edukatif. Evaluasi melalui pre-test dan post-test menunjukkan peningkatan pengetahuan sebesar 32%, sikap terhadap ODHA sebesar 25%, dan kesediaan menjadi agen edukasi sebesar 31%. Hasil menunjukkan pendekatan berbasis digital efektif dalam meningkatkan literasi kesehatan pemuda serta membangun agen perubahan komunitas. Guna keberlanjutan, diperlukan pengembangan fitur aplikasi yang lebih interaktif dan kolaborasi dengan Puskesmas setempat.